Synchrotron XRF imaging of Alzheimer's disease basal ganglia reveals linear dependence of high-field magnetic resonance microscopy on tissue iron concentration - Finnegan,ME; Visanji,NP; Romero-Canelon,I; House,E; Rajan,S; Mosselmans,JFW; Hazrati,LN; Dobson,J; Collingwood,JF (Journal of Neuroscience Methods, 2019)
Background: Chemical imaging of the human brain has great potential for diagnostic and monitoring purposes. The heterogeneity of human brain iron distribution, and alterations to this distribution in Alzheimer's disease, indicate iron as a potential endogenous marker. The influence of iron on certain magnetic resonance imaging (MRI) parameters increases with magnetic field, but is under-explored in human brain tissues above 7 T. New Method: Magnetic resonance microscopy at 9.4 T is used to calculate parametric images of chemically-unfixed post-mortem tissue from Alzheimer's cases (n = 3) and healthy controls (n = 2). Iron-rich regions including caudate nucleus, putamen, globus pallidus and substantia nigra are analysed prior to imaging of total iron distribution with synchrotron X-ray fluorescence mapping. Iron fluorescence calibration is achieved with adjacent tissue blocks, analysed by inductively coupled plasma mass spectrometry or graphite furnace atomic absorption spectroscopy. Results: Correlated MR images and fluorescence maps indicate linear dependence of R 2 , R 2 and R 2 ’ on iron at 9.4 T, for both disease and control, as follows: [R 2 (s −1 ) = 0.072[Fe] + 20]; [R 2 (s −1 ) = 0.34[Fe] + 37]; [R 2 ’(s −1 ) = 0.26[Fe] + 16] for Fe in μg/g tissue (wet weight). Comparison with Existing Methods: This method permits simultaneous non-destructive imaging of most bioavailable elements. Iron is the focus of the present study as it offers strong scope for clinical evaluation; the approach may be used more widely to evaluate the impact of chemical elements on clinical imaging parameters. Conclusion: The results at 9.4 T are in excellent quantitative agreement with predictions from experiments performed at lower magnetic fields.